Scalability of Networks and Services Third International Conference on Autonomous Infrastructure, Management and Security, AIMS 2009 Enschede, The Netherlands, June 30 - July 2, 2009, Proceedings - Sadre, Ramin; Pras, Aiko (Computer Communication Networks and Telecommunications,, 2009)
This book constitutes the refereed proceedings of the Third International Conference on Autonomous Infrastructure, Management and Security, AIMS 2009, held in Enschede, The Netherlands, during June 30 - July 2, 2009 under the auspices of IFIP. The 12 revised full papers and three short papers presented together with 8 papers of the AIMS PhD workshop were carefully reviewed and selected from 28 submissions to the main conference and 15 papers for the PhD workshop respectively. The papers are organized in topical sections on network resource management, overlays and P2P networks, network configuration and optimization, as well as monitoring and visualization.